Concept of Islamic credit card based on Malaysia - Uddin, Mohi; Hossin, M.M Ismail; Chowdhury, AHM Yeaseen; Islam, Mohd Aminul (Scholars Middle East Publishers, 2018)
The intention of this study is to consider the possibility of credit card usage intention with Islamic banks‟ customers. Concept of Islamic credit card was express in edict to greet out whether these are persuading the Islamic credit card usage intention otherwise not. It means a conceptual form toward design the features essential the Islamic credit card usage intention. The significance descriptions to “concept on Islamic credit card” are widely moving the Islamic credit card usage intention as well as terminate that to have no consequence on the Islamic credit card usage intention. Although it gives the hold up for prospect researches in the outlook of Islamic credit card and it favor the advantage to the academic awareness over detaching in a superior way tumble on affecting Islamic credit card usage intention. This particular significance is toward bank executives; given them through an enhanced conception pertaining to the Malaysian bank customers‟ usage intentions for Islamic credit cards also helps them toward better plan for Islamic credit card services, in edict to bring for the financial requirements of Malaysia bank customers. The attaining a additional weighty point of view of Malaysia bank customers‟ is usage intentions for Islamic credit cards as well as determine the accurately decide the use of Islamic credit cards throughout develops the literature on Islamic credit cards.